RC pile soil interaction analysis using a 3D-finite element method with fibre theory-based beam elements. - Maki, Takeshi
To evaluate the overall response of a structural system including its foundation and surrounding soil, an equivalent finite element model with reduced degrees of freedom using fibre theory-based beam element was proposed. The proposed model was based on investigations of the subgrade soil reaction of a single-layer model, and was verified for the cyclic behaviour of a laterally loaded single RC pile in terms of the load?displacement relationship, pile deformation, and soil pressures on the pile surface. Also investigated was the effect of the interfacial element between pile and soil on the behaviour of the laterally loaded pile.
Keywords: RC pile; Subgrade soil reaction; 3D-FEM analysis; Fibre model; Beam element; Interface between pile and soil